Investigation of 22 kV silane cure TR-EPR cable - Fernando Agustin; Akhtar Kalam; Aladin Zayegh (International Journal of Applied Power Engineering (IJAPE), 2021)
EPR-insulated cables for distribution power network are not commonly used in Australia. This is due to the higher DDF of common EPR cables when compared with XLPE that contributes to the power loss and economics in transmitting electricity. This led to the development of EPR called TR-EPR with significantly lower DDF and uses silane curing process to address concerns about cost-effectiveness. The thermal behavior of low DDF silane cure TR-EPR is investigated for 30 months of exposure to the maximum operating temperature of material. The physical changes in the samples throughout the long-term aging are examined to create an opportunity to model the expected life cycle of TR-EPR cable under thermal stress. The cross-linking characteristics of TR-EPR cable are also examined by ambient curing that simulates the storage condition for unused cable and by cable heating process that simulates the condition when the cable is energized. The results are tabulated for a better understanding of the time for the material to cross-link at various conditions. The improved partial discharge values after cross-linking are also presented.